2023
DOI: 10.1038/s41419-023-05969-9
|View full text |Cite
|
Sign up to set email alerts
|

The Road from AKI to CKD: Molecular Mechanisms and Therapeutic Targets of Ferroptosis

Abstract: Acute kidney injury (AKI) is a prevalent pathological condition that is characterized by a precipitous decline in renal function. In recent years, a growing body of studies have demonstrated that renal maladaptation following AKI results in chronic kidney disease (CKD). Therefore, targeting the transition of AKI to CKD displays excellent therapeutic potential. However, the mechanism of AKI to CKD is mediated by multifactor, and there is still a lack of effective treatments. Ferroptosis, a novel nonapoptotic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 146 publications
0
8
0
Order By: Relevance
“…Ferroptosis is a type of cell death that is different than apoptosis and necrosis, playing a role in the AKI-to-CKD transition [210]. Iron metabolism is a key factor in initiating the ferroptosis process via the accumulation of products of lipid peroxidation and overproduction of ROS [211,212]. Several cellular pathways involved in the AKI-to-CKD transition depend on ferroptosis (mitochondrial dysfunction, fibrosis) [213][214][215].…”
Section: Iron Death Pathways In the Aki-to-ckd Transitionmentioning
confidence: 99%
“…Ferroptosis is a type of cell death that is different than apoptosis and necrosis, playing a role in the AKI-to-CKD transition [210]. Iron metabolism is a key factor in initiating the ferroptosis process via the accumulation of products of lipid peroxidation and overproduction of ROS [211,212]. Several cellular pathways involved in the AKI-to-CKD transition depend on ferroptosis (mitochondrial dysfunction, fibrosis) [213][214][215].…”
Section: Iron Death Pathways In the Aki-to-ckd Transitionmentioning
confidence: 99%
“…Accumulating studies have shown that ferroptosis plays a role in the genesis of kidney diseases. 35 Accumulating evidence has shown epigenetic regulation of ferroptosis in kidney diseases, including acute kidney injury (AKI), 484 , 485 diabetic nephropathy (DN), 486 renal fibrosis, 487 renal IRI (RIRI), 488 492 sepsis-induced acute kidney injury (SAKI), 493 toxin-mediated kidney toxicity, 494 and crystal nephropathies. 495 Below, we summarize the epigenetic regulation of ferroptosis by phosphorylation, ncRNAs, deacetylation, and ubiquitination in kidney diseases (Table 12 and Fig.…”
Section: Epigenetic and Posttranslational Modifications Regulating Fe...mentioning
confidence: 99%
“…Dysregulated ferroptosis is increasingly recognized as a significant contributor to the pathogenesis of diseases, including cancers, 18 nervous system diseases (NSDs), 19 23 cardiovascular diseases (CVDs), 24 28 liver diseases, 29 , 30 lung diseases, 31 34 , and kidney diseases. 35 Recently, ferroptosis has been recognized to play an important role in halting tumor growth. 36 In the last decade, accumulating evidence has revealed the role of ferroptosis in tumor growth suppression and shown that ferroptosis induction partially mediates the tumor-suppressive effects of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ferroptosis is characterized by distinct morphological changes, including decreased mitochondrial volume, increased mitochondrial membrane density, and the absence of typical apoptotic features 4 . Dysregulation of ferroptosis has been linked to several illnesses including neurological conditions 5 - 7 , cardiovascular diseases 8 , 9 , acute and chronic kidney injury 10 - 12 , ischemia-reperfusion injury 13 , 14 , and cancer therapy 15 - 17 , making it an active research topic in cell biology and medicine.…”
Section: Introductionmentioning
confidence: 99%